2016
DOI: 10.1021/acsami.5b11120
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Porous Zeolite Structures for Pressure Swing Adsorption Applications

Abstract: Porous adsorbents with hierarchical structured macropores ranging from 1 to 100 μm are prepared using a combination of freeze casting and additional sacrificial templating of polyurethane foams, with a zeolite 13X powder serving as adsorbent. The pore system of the prepared monoliths features micropores assigned to the zeolite 13X particle framework, interparticular pores of ∼1-2 μm, lamellar pores derived from freeze casting of ∼10 μm, and an interconnected pore network obtained from the sacrificial templates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 37 publications
2
37
2
Order By: Relevance
“…Even so, there is limited literature on monoliths extruded with zeolites, although there has been renewed interest in the extrusion of monoliths with zeolites, particularly in the field of pressure-swing adsorption [178]. Pressure-swing adsorption offers an attractive alternative to the usual and expensive cryogenic separation of gases, for example, propane/propylene [179].…”
Section: Extruding Zeolites Into Monolithsmentioning
confidence: 99%
“…Even so, there is limited literature on monoliths extruded with zeolites, although there has been renewed interest in the extrusion of monoliths with zeolites, particularly in the field of pressure-swing adsorption [178]. Pressure-swing adsorption offers an attractive alternative to the usual and expensive cryogenic separation of gases, for example, propane/propylene [179].…”
Section: Extruding Zeolites Into Monolithsmentioning
confidence: 99%
“…The additional amount of binder is always chosen depending on the amount of zeolite and presented in dry weight basis (dwb %). For the powdery binders, namely bentonite and kaolin, the processing route based on our previous study 9 is used, as schematically shown in Figure 1A. First, PEG serving as the dispersant and organic temporary binder is dissolved in deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, to increase the efficiency of swing adsorption processes, zeolite powders are colloidal-processed to form monoliths with a hierarchical porosity. 39 Porous-structured monoliths feature superior heat-transfer properties for nonadiabatic processes and fast mass-transfer kinetics because diffusion on small scales is reduced to small path lengths. 1013…”
Section: Introductionmentioning
confidence: 99%
“…The detailed surface area and pore volume data are summarized in Table S2 in the Supporting Information. Table S4 in the Supporting Information summarizes the mechanical performance of reported structured zeolites manufactured by 3D printing (0.05-1.54 MPa) [32,33] or other shaping strategies, such as direct extrusion (2.58 MPa), [50] sacrificial templating (0.085 MPa), [16] pulsed current processing (1.6-2.2 MPa), [34] freeze casting (0.045-1.38 MPa), [15,51,52] and slip casting (0.21-0.75 MPa). The external surface area and mesopore volume of ZM-BF are 40 m 2 g −1 and 0.040 cm 3 g −1 , respectively, which are higher than the parental NaX powders (S ext = 32 m 2 g −1 and V mes = 0.017 cm 3 g −1 ), as a result of the mesoporous character of ZM-BF.…”
mentioning
confidence: 99%
“…Table S4 in the Supporting Information summarizes the mechanical performance of reported structured zeolites manufactured by 3D printing (0.05–1.54 MPa) or other shaping strategies, such as direct extrusion (2.58 MPa), sacrificial templating (0.085 MPa), pulsed current processing (1.6–2.2 MPa), freeze casting (0.045–1.38 MPa), and slip casting (0.21–0.75 MPa) . It is clear that ZM‐BF exhibits a much higher mechanical strength than most of the reported structured zeolites, which is only lower than that of 3D‐printed polymer‐zeolite composite monoliths .…”
mentioning
confidence: 99%